COMPARATIVE STUDY OF GROWTH AND YIELD PERFORMANCE OF VARIOUS CARROT CULTIVARS UNDER CLIMATIC CONDITIONS OF BALOCHISTAN - Ali, Malik; Lehir, Sher; Bangulzai, Bashir; Ahmed, Shafique; Babar, Muhammad; Nadeem, Mohammad; Kashif, Mohammad; Dawood, Mohammad; Langove, Abdul (American Journal of Agriculture, 2021)
Purpose: Comparative study of growth and yield performance of various carrot cultivars under climatic conditions of Balochistan Methodology: An experimental trial was conducted at Agriculture Research Vegetable Seed Production situated at Quetta, Balochistan. In order to determine the growth and yield of different carrot cultivars were collected throughout the country and planted during the year 2018 in three replicated randomized complete block design (RCBD) having a plot size of 6 m x 6 m (36 m2). Finding: Out of 10 cultivars of carrot for higher productivity, all the growth traits was statistically significant except no of leaves, the cultivar Faisalabad T-29 was recorded high yielding (54.47 tons/ha) root yield of carrot, followed by Long Red India (48.49 tons/ha), T29 (VSF)(44.91 tons/ha), Amech (41.69 tons/ha),New Croda (32.87 tons/ha), D-C-3 (30.64 tons/ha),D-C96 (27.65 tons/ha), MP- 4(25.42 tons/ha) and Orange(23.05 tons/ha) root yield of carrot, respectively. However, minimum root yield (18.20 tons/ha) of carrot was recorded in D-C-W. Unique contribution to theory and practice: Main aim of this study was to reveal the potential existing germplasm of carrots regarding their morphological aspect. Also this study has deep impact on growing communities of province